2011
DOI: 10.1186/1745-6673-6-19
|View full text |Cite
|
Sign up to set email alerts
|

Screening for tuberculosis and prediction of disease in Portuguese healthcare workers

Abstract: IntroductionResults of systematic screening of healthcare workers (HCWs) for tuberculosis (TB) with the tuberculin skin test (TST) and interferon-γ release assays (IGRA) in a Portuguese hospital from 2007 to 2010 are reported.MethodsAll HCWs are offered screening for TB. Screening is repeated depending on risk assessment. TST and QuantiFERON Gold In-Tube (QFT) are used simultaneously. X-ray is performed when TST is > 10 mm, IGRA is positive or typical symptoms exist.ResultsThe cohort comprises 2,889 HCWs. TST … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
33
1
1

Year Published

2013
2013
2016
2016

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 18 publications
2
33
1
1
Order By: Relevance
“…Thus, despite high specificity of the IGRA the diagnostic accuracy is low. Other studies assessing the predictive value in a low-endemic setting have found PPV of IGRA ranging from 0.8% in Portuguese healthcare workers22 and 2.4% among Dutch contacts who did not start preventive therapy8 to approximately 7%–8% in HIV positive10 23 to 28.6% in recently exposed children 21. Generally, above studies are limited by low number of incident TB cases ranging from 2 to 24 cases and variable design and follow-up periods 5 6 10 18 19 21 23.…”
Section: Discussionmentioning
confidence: 93%
“…Thus, despite high specificity of the IGRA the diagnostic accuracy is low. Other studies assessing the predictive value in a low-endemic setting have found PPV of IGRA ranging from 0.8% in Portuguese healthcare workers22 and 2.4% among Dutch contacts who did not start preventive therapy8 to approximately 7%–8% in HIV positive10 23 to 28.6% in recently exposed children 21. Generally, above studies are limited by low number of incident TB cases ranging from 2 to 24 cases and variable design and follow-up periods 5 6 10 18 19 21 23.…”
Section: Discussionmentioning
confidence: 93%
“…For example, Franchi and colleagues evaluated 1,755 HCWs in Italy in 2004, diagnosing LTBI in 6% of cases [18]; in a study conducted in France (a low-incidence country with 5.2 cases of TB per 100,000 inhabitants in 2006), 18.9% of 148 HCWs had a positive IGRA result [19]: and in a study on 134 HCWs in Spain (another low-incidence country), the pevalence of LTBI was 11.2% [20]. By contrast, a study on 2,884 hospital workers in Portugal (a high-incidence country, with 32 cases/100,000/year) reported a very high prevalence of LTBI (i.e., 29.5%) [21]. However, a 2005 meta-analysis reported that the prevalence of LTBI in HCWs ranged 5–55% in high-income countries [22].…”
Section: Discussionmentioning
confidence: 99%
“…Fifteen studies with a combined sample size of 26,680 participants were included in this analysis (107)(108)(109)(110)(111)(112)(113)(114)(115)(116)(117)(118)(119)(120)(121). The incidence of active TB during a median follow-up of 3 years was 2 to 24 per 1,000 person-years for IGRA-negative individuals (Fig.…”
Section: Predictive Value For Progression To Tb Diseasementioning
confidence: 99%